Potential biodiversity map of understory plants for Nothofagus forests in Southern Patagonia: Analyses of landscape, ecological niche and conservation values - Rosas, Yamina Micaela; Peri, Pablo Luis; Lencinas, María Vanessa; Martínez Pastur, Guillermo José (Science of The Total Environment, 2019)
The role of understory plants in native forests is critical for ecosystem function, wildlife protection and ecosystem productivity. The interest to estimate biodiversity increased during the last decades at landscape level. The objective was to elaborate a map of potential biodiversity (MPB) of understory species of Nothofagus forest using potential habitat suitability maps (PHS) of 15 plants in Santa Cruz province, Argentina. Additionally, we asked the following questions: (i) Were plant species differentially distributed according to the forest types?, (ii) do forest types represent different plant species assemblage with specific ecological niche requirements?, and (iii) is it possible to detect hotspots in the MBP according to the forest types? We used 721 plots database of vascular plants, from where 15 indicator species were identified. The assemblage species for different forests (Nothofagus antarctica, N. pumilio and evergreen mixed) were analysed using a detrended correspondence analysis. Also, we explored 41 potential explanatory variables to develop PHS, and combined these maps to obtain one MPB (1–100%). Finally, we analysed the outputs into a GIS through different landscapes alternatives to detect hotspot areas. Marginality and specialization values allowed identifying species assemblage that presented similar variability in the habitat requirements. MPB varied across the landscape, with higher values in the south and lower values near glaciers. MPB had the highest values in N. antarctica forest with >50% cover at landscape level. N. antarctica present more hotspots than N. pumilio forests, mainly in the south, compared to mixed evergreen forests which present few hotspots near glaciers. These results can be used as a tool to design new management and conservation strategies at landscape level. EEA Santa Cruz Fil: Rosas, Yamina Micaela. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Centro Austral de Investigaciones Cientificas. Laboratorio de Recursos Agroforestales; Argentina Fil: Peri, Pablo Luis. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Santa Cruz; Argentina. Universidad Nacional de la Patagonia Austral; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Lencinas, María Vanessa. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Centro Austral de Investigaciones Cientificas. Laboratorio de Recursos Agroforestales; Argentina Fil: Martínez Pastur, Guillermo José. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Centro Austral de Investigaciones Cientificas. Laboratorio de Recursos Agroforestales; Argentina